Analysis of desertification combating needs based on potential vegetation NDVI—A case in the Hotan Oasis - Zhang, Lei; Qu, Jia; Gui, Dongwei; Liu, Qi; Ahmed, Zeeshan; Liu, Yi; Qi, Zhiming (Frontiers in Plant Science, 2022)
Combating desertification is vital for arresting land degradation and ensuring sustainable development of the global ecological environment. This study has analyzed the current desertification status and determined its control needs based on the difference between potential NDVI (PNDVI) and actual NDVI (ANDVI) in the Hotan desertoasis. The MaxEnt model, combined with the distribution point data of natural vegetation with long-term stable NDVI and 24 environmental factors was used to predict the PNDVI spatial distribution of different vegetation coverage grades and compared it with ANDVI. Excluding the areas of intense human activity such as arable land, the simulation results show that PNDVI with high, medium, and low vegetation cover was mainly distributed in the southwest and southeast of Hotan Oasis, in the midstream and downstream of Kala Kashgar River and Yulong Kashgar River, and the desert or Gobi area outside the oasis, respectively. The distribution of PNDVI with high, medium, and low vegetation cover accounted for 6.80 %, 7.26 %, and 9.17 % of Hotan oasis, respectively. The comparison between ANDVI and PNDVI shows that 18.04% (ANDVI ＜ PNDVI, 3902.01km2) of the study area is still suffering from desertification, which is mainly distributed in the desert-oasis ecotone in Hotan. The findings of this study implied that PNDVI could be used to assess the desertification status and endorsement of desertification control measures in vulnerable ecosystems. Hence, PNDVI can strengthen the desertification combating efforts at regional and global scales and may serve as a reference point for the policymakers and scientific community towards sustainable land development.